Tools and concepts for understanding disruptive technological change after Schumpeter - Mark Knell; Simone Vannuccini (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
This chapter is about radical innovation and disruptive technological change. Discovering the nature and mechanisms of disruptive technological change can help to understand the long-run dynamics of innovation and map profound transformation in socio-economic systems. The chapter considers four concepts essential for the understanding radical and disruptive technological change: long waves, techno-economic paradigms, general purpose technologies (GPTs), and disruptive technologies. We conclude with some insights on the emerging technologies in the latest techno-economic paradigm. The tools and concepts given here remain the cornerstone of a useful theory of innovation and change even in our current complex sociotechnical landscape.
Keywords: 330; Radical innovation; Kondratiev; long wave cycle; Schumpeter; perennial gale of creative destruction; technological discontinuities; techno-economic paradigm; technological revolution; great surge of development; general purpose technology; disruptive technology; emerging technology